Preparation and characterization of hypercrosslinked poly (HEMA-co-EGDMA-co-VBC) - Mohammad Zuhaili, Yahya; Norhayati, Abdullah (Indian Society for Education and Environment & Informatics Publishing Limited, 2017)
Objectives: The aims of this paper was to produce hydroxyl hypercrosslinked polymers with high specific surface area derived from poly(HEMA-co-EGDMA-co-VBC) precursor beads. Methods: This was achieved using hypercrosslinking reaction and the beads were characterized by FTIR, SEM and BET analysis.